Organization of coordination and logistics center (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article discusses the problems that do not allow organizing passenger transportation that meets modern requirements for transport services to the population. Known ways and methods that make it possible to improve the level of transport services for the population are considered, and the automated information and control systems of the transport complex operating in Osh, aimed at improving the quality of passenger transportation, are presented. Based on the comparative analysis method, it is recommended to create a coordination and logistics center that allows saving personal time and money, reducing transport fatigue, choosing the optimal route, attracting potential passengers through confidence in the timeliness of the trip, choosing the optimal route and saving the passenger’s personal time.
Keywords: urban passenger transport; traffic flow; intensity; traffic delays; passenger traffic; capacity